1985
DOI: 10.3406/rural.1985.3104
|View full text |Cite
|
Sign up to set email alerts
|

Rente pétrolière et crise agricole.

Abstract: Oil Revenues and the Agricultural Crisis. Among developing countries, oil-producers rank first in terms of food deficit. Thanks to the two oil booms, these exporting economies had no problems solving traditional agricultural development problems, namely deficit financing and the insolvency of the internal market. But the massive inflow of oil revenues determines an economic development pattern that destabilizes rather than supports the agricultural sector. The state monopoly over oil revenues led t… Show more

Help me understand this report

Search citation statements

Order By: Relevance

Paper Sections

Select...
2

Citation Types

0
2
0
1

Year Published

1991
1991
2018
2018

Publication Types

Select...
3
1

Relationship

0
4

Authors

Journals

citations
Cited by 4 publications
(3 citation statements)
references
References 0 publications
0
2
0
1
Order By: Relevance
“…The oil-producing countries are scarcely different from the majority of developing countries that have been seen to steadily increase over the past decades, the deficit in food and often deepening structural crisis in agriculture. As pointed by Egg et al (1985) the oil rent distribution model seems to have systematically favored urban and import sectors at the expense of rural and domestic production. In the agricultural sector, even more than for other economic activities, the states whose financial power (and thus political and economic ones) has increased significantly have been unable to get around the spontaneous effects of rent diffusion in national economies.…”
Section: Relevant Literaturementioning
confidence: 99%
See 1 more Smart Citation
“…The oil-producing countries are scarcely different from the majority of developing countries that have been seen to steadily increase over the past decades, the deficit in food and often deepening structural crisis in agriculture. As pointed by Egg et al (1985) the oil rent distribution model seems to have systematically favored urban and import sectors at the expense of rural and domestic production. In the agricultural sector, even more than for other economic activities, the states whose financial power (and thus political and economic ones) has increased significantly have been unable to get around the spontaneous effects of rent diffusion in national economies.…”
Section: Relevant Literaturementioning
confidence: 99%
“…Egg, Lerin and Tubiana (1985) showed that the proliferation of oil rent based economies in the 1970s and their increasing participation in global economic exchanges generate a number of established ideas about the global food system. The oil-producing countries are scarcely different from the majority of developing countries that have been seen to steadily increase over the past decades, the deficit in food and often deepening structural crisis in agriculture.…”
Section: Relevant Literaturementioning
confidence: 99%
“…Les contrecoups sur le secteur agricole, sans avoir l'ampleur de ceux constatés dans le cas désormais connu du Nigeria, sont plus nuancés(EGG et al, 1985 ;SCHERR, 1989) du fait de la différence des politiques sectorielles et de la protection des marchés intérieurs. Nous verrons plus loin comment la situation camerounaise restera relativement atypique, pendant que l'Indonésie réussira à réinvestir et à protéger, alors que le Mexique aura plus de difficultés à enrayer le phénomène malgré l'essai de politiques sectorielles volontaristes.…”
unclassified